Le thème littéraire du linceul et du satire du Seigneur depuis les témoignages des apocryphes jusqu'à ceux des récits de pèlerinages - Feiertag, Jean Louis (Apocrypha, 1999)
We can find the first known testimony about the preservation of Jesus's mortuary clothes in the Consultationes Zacchaei et Apollonii (about 410). A study of the history of the belief in their preservation has to consider the fact that different traditions circulated together and reinforced each other: some texts speak only about the transmission of the shroud or the sudarium from Jesus to someone else, or show them after the Resurrection (Gospel according to the Hebrews, Acta Pilati, Gospel of Gamaliel and Lamentation of Mary), but other sources say that they are still extant, and even indicate sometimes their location (Consultationes Zacchaei, Pseudo Antoninus of Piacenza, Adamnanus). The likely reading of the Gospel according to the Hebrews and the Acta Pilati in circles already more or less convinced of the preservation of the shroud or the sudarium leads to the conclusion that such texts have reinforced the belief in their preservation.